New Diagnostic Assays for Differential Diagnosis Between the Two Distinct Lineages of Bovine Influenza D Viruses and Human Influenza C Viruses - Okda, Faten A.; Griffith, Elizabeth; Sakr, Ahmed; Nelson, Eric; Webby, Richard (Frontiers in Veterinary Science, 2020)
Influenza D virus (IDV), a novel orthomyxovirus, is currently emerging in cattle worldwide. It shares >50% sequence similarity with the human influenza C virus (HICV). Two clades of IDV are currently co-circulating in cattle herds in the U.S. New assays specific for each lineage are needed for accurate surveillance. Also, differential diagnosis between zoonotic human influenza C virus and the two clades of IDV are important to assess the zoonotic potential of IDV. We developed an enzyme-linked immunosorbent assay (ELISA) based on two different epitopes HEF and NP and four peptides, and fluorescent focus neutralization assay to differentiate between IDV bovine and swine clades. Calf sera were obtained, and bovine samples underwent surveillance. Our results highlight the importance of position 215 with 212 in determining the heterogeneity between the two lineages. We needed IFA and FFN for tissue culture–based analysis and a BSL2 facility for analyzing virus interactions. Unfortunately, these are not available in many veterinary centers. Hence, our second aim was to develop an iELISA using specific epitopes to detect two lineages of IDVs simultaneously. Epitope-iELISA accurately detects neutralizing and non-neutralizing antibodies against the IDV in non-BSL2 laboratories and veterinary clinics and is cost-effective and sensitive. To differentiate between IDVs and HICVs, whole antigen blocking, polypeptides, and single-peptide ELISAs were developed. A panel of ferret sera against both viruses was used. Results suggested that both IDV and ICV had a common ancestor, and IDV poses a zoonotic risk to individuals with prior or current exposure to cattle. IDV peptides IANAGVK (286–292 aa), KTDSGR (423–428 aa), and RTLTPAT (448–455 aa) could differentiate between the two viruses, whereas peptide AESSVNPGAKPQV (203–215 aa) detected the presence of IDV in human sera but could not deny that it could be ICV, because the only two conserved influenza C peptides shared 52% sequence similarity with IDV and cross-reacted with IDV. However, blocking ELISAs differentiated between the two viruses. Diagnostic tools and assays to differentiate between ICV and IDV are required for serological and epidemiological analysis to clarify the complexity and evolution and eliminate misdiagnosis between ICV and IDV in human samples.